2013
DOI: 10.1542/peds.2013-0143
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Masked, Placebo-Controlled Study of Darbepoetin Alfa in Preterm Infants

Abstract: BACKGROUND: A novel erythropoiesis stimulating agent (ESA), darbepoetin alfa (Darbe), increases hematocrit in anemic adults when administered every 1 to 3 weeks. Weekly Darbe dosing has not been evaluated in preterm infants. We hypothesized that infants would respond to Darbe by decreasing transfusion needs compared with placebo, with less-frequent dosing than erythropoietin (Epo). METHODS: Preterm infants 500 to 1250 g birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
93
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 41 publications
0
93
0
7
Order By: Relevance
“…We previously reported that preterm infants randomized to Epo and Darbe received half the number of transfusions and were exposed to half the donors compared with the placebo group. 12 Based on its potential for neuroprotection, our study was designed to determine whether Darbe was also effective in improving developmental outcomes. …”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that preterm infants randomized to Epo and Darbe received half the number of transfusions and were exposed to half the donors compared with the placebo group. 12 Based on its potential for neuroprotection, our study was designed to determine whether Darbe was also effective in improving developmental outcomes. …”
Section: Resultsmentioning
confidence: 99%
“…Since the early 1990s, a number of studies have explored whether erythropoietin (Epo) administration could help to reduce the number of or need for packed red cell transfusions in neonates with the anemia of prematurity [10]. Epo stimulates a crucial signaling pathway that promotes erythroid progenitor and precursor survival, proliferation, and differentiation ( Fig.…”
mentioning
confidence: 99%
“…In a recent study from Ohls et al, a randomized, placebo-controlled trial was performed to test whether either Epo or the longer-acting Epo analog darbepoetin alfa (Darbe) can reduce the need for transfusions, while also measuring the incidence of morbidities of concern in these groups, such as the ROP [10]. The authors provided preterm infants with birth weights between 500 and 1250 g who were less than 48 hr at the time of enrollment, with either weekly Darbe treatment at 10 mg/kg subcutaneously or Epo at 400 U/kg three times per week subcutaneously.…”
mentioning
confidence: 99%
See 2 more Smart Citations